26. TREATMENT OF PROXIMAL POLE SCAPHOID NONUNION USING VASCULARIZED BONE GRAFT AND INTERNAL FIXATION: A CASE REPORT AND LITERATURE REVIEW (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the outcomes of treating proximal scaphoid nonunion using vascularized bone grafting combined with internal fixation.Materials and methods: A 38-year-old right-handed male patient sustained a fall over 5 years ago and was initially misdiagnosed with a wrist sprain. He continued to experience pain and limited range of motion in the right wrist (flexion 30°, extension 10°). X-rays revealed a proximal pole scaphoid nonunion with changes in bone density but no evident 'humpback' deformity. We decided to perform a vascularized bone graft using the 1,2 intercompartmental supraretinacular artery (ICSRA) and fix the graft with 1.25 mm threaded Kirschner wires. Surgical technique: the vascularized bone graft was harvested from the dorsal aspect of the distal radius based on the 1,2-ICSRA, following the technique described by Zaidemberg. Necrotic bone was debrided and replaced with cancellous bone harvested from the iliac crest. Fixation was performed using two 1.25 mm threaded Kirschner wires and one additional wire to stabilize the vascular pedicle under fluoroscopic guidance. Postoperative care: the wrist was immobilized in a plaster thumb-spica cast for 8 weeks, followed by removable splinting and rehabilitation. Radiographs were taken at regular intervals to monitor bone healing.Results: At 5 months postoperatively, radiographs confirmed complete bone union. At the 2-year follow-up, the patient achieved 45° of wrist flexion and 70° of extension. Grip strength improved from 10 kg to 30 kg. The VAS pain score was 0 at rest and 1 during activity. The patient resumed normal daily activities without pain or functional limitation.Conclusion: For cases of proximal scaphoid nonunion with osteonecrosis, the combination of vascularized bone grafting and fixation with threaded Kirschner wires yields favorable outcomes, providing stable fixation of the proximal bone fragment and promoting bone healing.
Keywords: Proximal scaphoid nonunion; a vascular necrosis; vascularized bone graft; intercompartmental supraretinacular artery 1, 2.